2009
DOI: 10.1007/s11519-009-0038-8
|View full text |Cite
|
Sign up to set email alerts
|

How can organisations learn: an information systems development perspective

Abstract: This article sets out to argue that organisations can learn but that they cannot do so in their own right without infrastructural support. This article further examines the notion that individuals in organisations also require the cognitive participation of the organisation itself as a learning entity to learn. The close reliance and affiliation required between individuals and organisations to enable their learning from one another are discussed. In continuation of this, specific examples are provided through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…It provides a way to store and access required memory and knowledge rapidly by using internet, WWW, WAN, intranet or LAN and any other ICTs (Bennet and Shane Tomblin 2006;Chalmeta and Grangel 2008;Croasdell 2001). Organizations use various information systems for acquisition, retention, transfer and application of required knowledge to obtain competitive advantages and meet their objectives (Arias and Solana 2013;Baxter et al 2009;Chou 2003;Davison et al 2013;Hrastinski and Monstad 2014;Lyytinen and Rose 2006;Ruiz-Mercader et al 2006). Janson et al (2007) demonstrated role of information technology to support an organization to learn for successful transition from a socialist company to a privatized company.…”
Section: Information Technology For Organizational Learningmentioning
confidence: 99%
“…It provides a way to store and access required memory and knowledge rapidly by using internet, WWW, WAN, intranet or LAN and any other ICTs (Bennet and Shane Tomblin 2006;Chalmeta and Grangel 2008;Croasdell 2001). Organizations use various information systems for acquisition, retention, transfer and application of required knowledge to obtain competitive advantages and meet their objectives (Arias and Solana 2013;Baxter et al 2009;Chou 2003;Davison et al 2013;Hrastinski and Monstad 2014;Lyytinen and Rose 2006;Ruiz-Mercader et al 2006). Janson et al (2007) demonstrated role of information technology to support an organization to learn for successful transition from a socialist company to a privatized company.…”
Section: Information Technology For Organizational Learningmentioning
confidence: 99%
“…Higher level (team and organizational level) learning cannot occur without the existence of individual learners (Baxter et al, 2009). The individual's cognitive process (such as inquiry and reflection) drives knowledge creation and learning.…”
Section: The Multilevel Approach To Investigate Learning In Organizatmentioning
confidence: 99%
“…The analysis begins by asking the question, "what is learning in the context of an organization?" Researchers have offered different ways to describe this phenomenon (Baxter, Connolly, & Stansfield, 2009;Fenwick, 2008). For the purpose of this discussion, Elkajer's (2001) definition of learning will be adopted.…”
Section: The Multilevel Approach To Investigate Learning In Organizatmentioning
confidence: 99%
See 2 more Smart Citations